If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(h + -3) = 24 Reorder the terms: 2(-3 + h) = 24 (-3 * 2 + h * 2) = 24 (-6 + 2h) = 24 Solving -6 + 2h = 24 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2h = 24 + 6 Combine like terms: -6 + 6 = 0 0 + 2h = 24 + 6 2h = 24 + 6 Combine like terms: 24 + 6 = 30 2h = 30 Divide each side by '2'. h = 15 Simplifying h = 15
| 2/3x=4x+10 | | x^2-10x+50=10x | | 4m+6=22 | | 12y+11=24y+9 | | m=5-8 | | 43*6= | | -5(x+3)= | | 14x-2=-12x+70 | | n=210+6 | | 4(x-3)-5=2x+3 | | n=2m+6 | | 3n*3n=75 | | 7x-105=3x-13 | | -2(x-5)+8x=9x-6 | | (8+6i)+(4-3i)=0 | | 109-3x=15x-21 | | 3x-5=4x-2 | | -15+n=-27 | | -2x-58=2-4x | | -x/6 | | 3-4-6/x=12 | | 5-3x=2x+9+3x | | 2(7bx+y)=13bx-3y | | 20+4x=30 | | -3x+6-1=12 | | 4-1-2y=8 | | -2x+14=-16 | | -2x+(-24)=-18 | | 2/3x-1/6=-7 | | -6(10-4x)=3(-12-8x) | | x=23-5y | | -3x-13=-4 |